Pex for Fun: Engineering an Automated Testing Tool for Serious Games in Computer Science - Tillmann, Nikolai; Halleux, Jonathan "Peli" de; Xie, Tao (2011)
Although there are various emerging serious games developed for education and training purposes, there exist few serious games for practitioners or students to improve their programming or problem-solving skills in the computer science domain. To provide an open platform for creating serious games in learning computer science, we have developed a web‐based serious gaming environment called Pex for Fun, in short Pex4Fun (http://www.pexforfun.com/), for learning critical computer science skills such as problem solving skills and abstraction skills. It works on any web‐enabled device, even a smart phone. It comes with an auto‐completing code editor, providing a user with instant feedback similar to the code editor in Microsoft Visual Studio. It is a cloud application with the data in the cloud, enabling a user to use it anywhere where an Internet connection is available. New learners of programming can play games there created by us to master basic programming concepts such as arrays, loops, and exception handling. In fact, any user can create new games for others to play.